Guttural pouch mycosis in horses: a retrospective study of 28 cases - Dobesova, O; Schwarz, B; Velde, K; Jahn, P; Zert, Z; Bezdekova, B (The Veterinary record, 2012)
The medical records of 28 horses with guttural pouch mycosis were reviewed. The most commonly observed clinical signs were nasal discharge, epistaxis, dysphagia and/or cough. All 28 horses had the disease unilaterally, however, in five of them, it had spread into the contralateral pouch via the mesial septum. Three horses were treated medically, 11 horses underwent surgery and seven horses were treated both medically and surgically. Fifty percent of horses (14/28) were euthanased or died, fifty percent of horses (14/28) survived. There was no significant correlation between treatment method (medical, surgical, combination) and survival rate. The most common reason for euthanasia was dysphagia due to pharyngeal dysfunction. There was a highly significant correlation between the presence of dysphagia and non-survival (p=0.008).
Keywords: Horse Diseases; retrospektivní studie; zvířata; Otorhinolaryngologic Diseases; Combined Modality Therapy; Deglutition Disorders; koně; Antifungal Agents; mužské pohlaví; poruchy polykání; antifungální látky; nemoci koní; výsledek terapie; kombinovaná terapie; mykózy; Treatment Outcome; Horses; ženské pohlaví; Animals; Mycoses; otorinolaryngologické nemoci; analýza přežití; Male; Retrospective Studies; Survival Analysis; Female